Schwann Cell Development and Pathology - Sango, Kazunori.; Sango, Kazunori.; Yamauchi, Junji.; Yamauchi, Junji. (Springer Japan : Imprint: Springer, 2014)
This book presents recent topics on the development, differentiation, and myelination of Schwann cells, as well as pathological mechanisms and therapeutic approaches for peripheral neuropathies, such as Charcot–Marie–Tooth diseases, amyloid polyneuropathy, immune-mediated neuropathy, and diabetic neuropathy. The rapid progress of molecular biological techniques in the last decades, especially for RNA techniques and gene modification technologies, have allowed us to investigate the pathobiology of Schwann cells in vivo and in vitro. Studies combining recent stem cell biology with recent biotechnology, which is now closely linked to physicochemical fields, further explain how Schwann cell lineages develop, a process that has long been thought to be very complicated in vivo. The findings contribute to the elucidation of fundamental mechanisms during development and under pathological conditions. We now know that these are closely tied to each other. This book also introduces unique coculture systems to reproduce the neuron–Schwann cell interplay during development, degeneration, and regeneration. Up-to-date research topics with high-quality immunofluorescence and electron micrographs introduced by young and energetic contributors are sure to arouse the readers' interest in Schwann cell biology. Discussion from the viewpoint of basic and clinical neuroscience makes the book educational for researchers, medical students, and young clinicians.